2011
DOI: 10.2196/jmir.1796
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use for Health-Related Information via Personal Computers and Cell Phones in Japan: A Cross-Sectional Population-Based Survey

Abstract: BackgroundThe Internet is known to be used for health purposes by the general public all over the world. However, little is known about the use of, attitudes toward, and activities regarding eHealth among the Japanese population.ObjectivesThis study aimed to measure the prevalence of Internet use for health-related information compared with other sources, and to examine the effects on user knowledge, attitudes, and activities with regard to Internet use for health-related information in Japan. We examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
84
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 50 publications
18
84
0
2
Order By: Relevance
“…This is an encouraging result. As might be expected, 11,22,23,43,44 uses of computer, Internet, and mobile phone were strongly related to the acceptance of e-health services both generally and in particular types of e-health applications. Women predominated among ehealth supporters (women, 61%; men, 39%).…”
Section: Discussionsupporting
confidence: 62%
“…This is an encouraging result. As might be expected, 11,22,23,43,44 uses of computer, Internet, and mobile phone were strongly related to the acceptance of e-health services both generally and in particular types of e-health applications. Women predominated among ehealth supporters (women, 61%; men, 39%).…”
Section: Discussionsupporting
confidence: 62%
“…35,45,47,[49][50][51][52] This effect was also seen in surveys carried out in the general population. 30,53,54 The surveys conducted among patients with malignant or chronic conditions do not confirm the effect of the severity of symptoms, disease stage, or disease duration on the health-related use of the Internet. 43,46,51,55 Our survey demonstrated that the relationship between the acceptance of e-health services and the intensity of the burden resulting from the disease (duration of chronic condition) is not straightforward.…”
Section: Factors Affecting the Acceptance Of E-health Applicationsmentioning
confidence: 98%
“…Contrary to the results of our study, surveys performed among the general population usually show significant differences in terms of the use or acceptance of the Internet for health-related activities depending on sex 27,29,30,56 or place of residence. 27,29,54,[57][58][59] As for hospitalization related to chronic disease, one could expect that more frequent contact with the healthcare system would increase patients' acceptance of e-health solutions. However, this was not confirmed by our study.…”
Section: Factors Affecting the Acceptance Of E-health Applicationsmentioning
confidence: 99%
“…Limited population-based studies are available to obtain a more precise profile of the Internet use and access to health information among various age groups, including the elderly. While [43] claimed that some of the strongest growth in the Internet use will be seen among the elderly populations with nearly 50% of this group was expected to be online by 2005, the growth continues to be slow among the elderly with only 29% using this medium in 2010 [16,44]. In Canada and around the world, the elderly cohort is the fastest growing segment of the population.…”
Section: Introductionmentioning
confidence: 99%